Study of histopathological spectrum of gallbladder in cholecystectomy specimens - Srinivasan, Gomathi; Sekar, A. Sagaya Inba (International Journal of Research in Medical Sciences, 2019)
Background: Cholecystitis is one of the most common indications for abdominal surgery. Routine examination of gallbladder grossly and microscopically shows lot of interesting findings. This study aims to quantify the various outcomes of routine gallbladder examination following cholecystectomy procedure. Methods: All clinical details and data from case sheet and patient history are collected and analysed for all the patients who underwent cholecystectomy surgery in the Department of General Surgery, Govt. Omandurar Medical College, Chennai, from August 2017 to August 2018. The Study period of this study was from August 2017 to August 2018. Three sections each from neck, body and fundus taken. Tissues were processed in automated tissue processor and paraffin blocks made. Statistical analysis of the data was done. Results: Total number of specimens received were 36. And among the cases the number of females were 33 and the number of males were 3. The number of cases of calculous cholecystitis were 31 and the number of cases with pigment stones were 26, number of cases with cholesterol stone were 2 and the number of cases with mixed stones were 3. The number of cases of acalculous cholecystitis were 5. The number of cases of cholecystectomy by laproscopy were 30 whereas the number of cases of cholecystectomy by open procedure were 6. Chronic cholecystitis was seen in 34 cases and chronic cholecystitis with stones was seen in 29 cases and chronic cholecystitis without stones was seen in 5 cases and Acute on chronic cholecystitis with pigment stone was seen in 1 case and xanthogranulomatous cholecystitis with pigment stone was seen in 1 case. Conclusions: The risk factors for developing chronic cholecystitis was seen in female gender. The predominant histomorphological pattern seen in this study group is chronic calculous cholecystitis. And the predominant type of stone found in this study is pigment stone compared to mixed and cholesterol stone.